Development of Mobile Application for Sustainable Creative Tourism Assessment using Confirmatory Factor Analysis Approach - Suphachaimongkol, Chitralada; Ratanatamskul, Chavalit; Silapacharanan, Siriwan; Utiswannakul, Patcha (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Creative tourism has received increasing attention. At present, the concept of creative tourism is still in development stage since there are few or no indicators for assessing the potential of creative tourism to area-based sustainable goals. This document aims to introduce the process of mobile application for sustainable creative tourism (SCT) model development using confirmatory factor analysis (CFA) approach. The study was divided into 4 phases. The first phase involved establishing elements, indicators and criteria drawn from some previous studies and the opinions of experts’ judgement in this study. Secondly, indicators and criteria were selected by using Delphi technique. Thirdly, the indicators and criterias were confirmed by utilizing CFA, Finally, the prototype of SCT mobile application assessment tool is proposed for SCT in this study, based on CFA. Tools for the study included: 1) structured questionnaire from reviews of literature for interviewing the expert, 2) questionnaire for Delphi techniques among the experts for collecting an opinion about the selection of the indicators, and 3) a questionnaire to assess the possibility of data collection concerning the components and indicators of SCT. 300 samples from creative tourism enterprises from all around Thailand were collected and 253 were responded. Data analysis was conducted by using descriptive statistics and CFA. The study found that SCT model consists of 8 components and 36 indicators. The finding from our research shows that it is eligible to establish the novel SCT assessment indicators. The result of SCT application model is appropriate to develop mobile application for SCT assessment tool.